2020
DOI: 10.4025/jphyseduc.v31i1.3106
|View full text |Cite
|
Sign up to set email alerts
|

Tactical and technical performance analysis of the male 65 kg category at the brazilian shotokan karate championship

Abstract: RESUMOO objetivo do presente estudo foi identificar as técnicas mais utilizadas por medalhistas e atletas derrotados durante o Campeonato Brasileiro de Karatê Shotokan de 2017. Onze lutas envolvendo treze atletas com 28.5 ± 3.7 anos que disputaram a categoria 1º. KYU até 65 kg foram investigados. A análise foi realizada por seis especialistas por meio da observação e registro de técnicas utilizando planilha tática e técnica de Scout de Karatê. O teste Anova foi utilizado para comparar as ações e técnicas mais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…This is in accordance with the research by Pitter Laird and Koropanovski which showed that the Gia Kuzuki technique was the highest-scoring technique (2,13) and with the research by Alinaghipour which found kizama zuki technique as the most scoring technique (14). Also, our research results are contrary to those found by Romanovitch, who found mawashi geri technique as the most applicable technique (18). In this research, kizama zuki had the highest frequency among the techniques studied, but the ratio of repetition of this technique to its scoring is in the third rank.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in accordance with the research by Pitter Laird and Koropanovski which showed that the Gia Kuzuki technique was the highest-scoring technique (2,13) and with the research by Alinaghipour which found kizama zuki technique as the most scoring technique (14). Also, our research results are contrary to those found by Romanovitch, who found mawashi geri technique as the most applicable technique (18). In this research, kizama zuki had the highest frequency among the techniques studied, but the ratio of repetition of this technique to its scoring is in the third rank.…”
Section: Discussioncontrasting
confidence: 99%
“…In high-level karate athletes, the use of punches is more commonly observed, thus, resulting in a greater potential for fatigue (Loturco et Petrov et al, 2018;ACMS, 2012, Tabben et al, 2015. On the other hand, other researchers found that the most frequent attack used by Brazilian National karate athletes was the semi-circular kick with the leg positioned behind (lower limb) (Ribas et al, 2020). Unfortunately, we did not determine the number of kicks and punches during each kumite fight to establish a comparison with these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Karate is an ancient martial art practiced by around 100 million people worldwide (Martínez et al, 2020). In karate competitions, the modalities used are kata and Shiai kumite, requiring athletes to possess physical and motor skills to perform different movements, such as punches, strikes, and kicks (Ribas et al, 2020;Voltarelli et al, 2009). During a kumite fight, movements need to be performed at maximum speed, ensuring that the attacker's hand or foot reaches the target without the opponent being able to respond (Przybylski, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Technical performance is related to the quality of attacking movements such as punches and kicks to blocks and defensive locks (Barley & Harms, 2021). Improving technical skills could support athletes to gain high performance, and has a great chance to win the com-petition (Ribas et al, 2020). Data from a previous study reported that in combat sports competition, athletes must carry out motoric actions in attacking and defending for 3 rounds of 5 minutes each, which means that the quality of technical performance is a crucial factor (Folhes et al, 2023;Manolachi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%